2008
DOI: 10.1074/jbc.m803046200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Construct of a Human Poly(C)-binding Protein Containing the First and Second KH Domains Reveals Insights into Its Regulatory Mechanisms

Abstract: Poly(C)-binding proteins (PCBPs) 2 are KH (hnRNP-K-homology) domain-containing proteins that specifically recognize poly(C) D/RNA sequences (1, 2). There are five PCBPs in mammalian cells: PCBP1-4 and hnRNP K. Each PCBP contains three KH domains: two consecutive domains at the N terminus and a third domain at the C terminus; an intervening sequence of variable length is present between the second and third domains (Fig. 1A).PCBPs regulate gene expression at various levels, including transcription, mRNA proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 48 publications
3
74
0
Order By: Relevance
“…It is also similar to that observed in the crystals of isolated KH domains, for example, between symmetry-related Nova-1 KH3 domains (Lewis et al 1999) or symmetry-related PCBP2 KH1 domains (Supplemental Fig. 2C, right panel; Du et al 2005Du et al , 2008. The KH2-KH5 architecture of GLD-3 does not show the other type of interface reported from crystals of isolated KH domains, namely, a helix-helix packing between symmetry-related a3-helices as seen in Nova-2 KH3 (Lewis et al 1999;Valverde et al 2008).…”
Section: Resultssupporting
confidence: 57%
“…It is also similar to that observed in the crystals of isolated KH domains, for example, between symmetry-related Nova-1 KH3 domains (Lewis et al 1999) or symmetry-related PCBP2 KH1 domains (Supplemental Fig. 2C, right panel; Du et al 2005Du et al , 2008. The KH2-KH5 architecture of GLD-3 does not show the other type of interface reported from crystals of isolated KH domains, namely, a helix-helix packing between symmetry-related a3-helices as seen in Nova-2 KH3 (Lewis et al 1999;Valverde et al 2008).…”
Section: Resultssupporting
confidence: 57%
“…Functional annotation analysis identified the top four significantly overrepresented cellular process gene classifications (and number of genes) as transcription (569), cell cycle (248), ubiquitin cycle (225), and cell division (115), whereas the top four overrepresented molecular function classifications were ligase activity (159), protein binding (1,810), nucleotide binding (774), and ATP binding (638). The top four significantly overrepresented GenMAPP pathway gene classifications were cell cycle/KEGG (56), mRNA processing reactome (63), RNA transcription reactome (28), and G1 to S cellcycle reactome (41). These data suggested that TUC338 could modulate cellular processes involved in cell growth.…”
mentioning
confidence: 81%
“…The sequence of TUC338 overlaps with that of PCBP2, an RNA binding protein involved in mRNA processing in humans (40)(41)(42). Interestingly, exonic ultraconserved regions are frequently associated with RNA processing, such as RNA binding or RNA splicing, suggesting a potential role as regulators of RNA.…”
Section: Discussionmentioning
confidence: 99%
“…The use of these preformed dimeric modules is especially suited for proteins that interact with short conserved RNA sequences and act on many targets, such as observed for PTB (Oberstrass et al 2005), Nova (Teplova et al 2011), and MBNL (Teplova and Patel 2008), involved in splicing regulation; ZBP1 (Patel et al 2012), involved in pre-mRNA localization; and polyC-binding protein (Du et al 2008), involved in multiple DNA and RNA regulation mechanisms. Although the arrangement of the STAR dimer is more complex, as it involves three domains connected by flexible linkers rather than one globular domain, the rationale for the use of dimerization is the same: targeting a pair of RNA sequence elements separated by a spacer of sufficient length and thereby modulating spatial arrangement of the RNA ligand.…”
Section: Contribution Of Protein Dimerization To Rna Target Selectionmentioning
confidence: 99%